The Safety Properties of Sodium Alginate and its Derivatives - Sharfi, Laleh; Nowroozi, Mohammad Reza; Smirnova, Galina; Fedotova, Anna; Babarkin, Dmitry; Mirshafiey, Abbas (British Journal of Healthcare and Medical Research, 2024)
Alginate is a biomaterial with a vast use in biomedicine, food and pharmaceutical industry due to its advantageous properties such as abundance, biocompatibility and easiness of gelation. The Food and Drug Administration (FDA) has confirmed some alginates salts and related derivative to “generally regarded as safe” components for oral use. According to the vast use of alginate as a harmless agent in food and pharmaceutical industries, logically its hydrolysate and ultimately its residues including Mannuronic and Guluronic acids, as alginate hydrolysate components are safe and non-toxic ingredients. In this regard, a number of studies have been conducted to reveal the safety of these agents. Hear, we aimed to review the safety of sodium alginate and its hydrolysate in the literature. In conclusion, the outcomes of acute and chronic toxicity studies indicate that the sodium alginate and its hydrolysate have a high safety profile when administered orally to animals.